Ambiguous Visualities: Gender, Governmentality and Graffiti in Urban India - Khurana, Sanchita (Contemporary Visual Culture and Art, 2026)
This paper examines a series of murals produced by a street art collective in an Indian city, situating them within the rapid expansion of state- and privately commissioned street art projects across Indian urban centres over the last decade. While street art has historically been associated with claims to urban democracy and challenges to elite cultural authority, its recent institutionalization within city-led beautification and revitalization programmes signals a significant shift in its political and administrative function. In contemporary Indian cities marked by rapid financialization, speculative urban development, and cultural regeneration, street art increasingly operates at the intersection of symbolic inclusion and material exclusion. Focusing on murals that foreground feminist and transgender themes, the paper analyzes how visual languages of gender justice, empowerment, and inclusion are mobilized within officially sanctioned urban art projects. These murals draw upon the moral economy of the “right to the city” discourse, invoking ideas of visibility, belonging, and public recognition for marginalized gendered subjects. At the same time, the conditions of their commissioning, funding, and spatial placement embed them within a political economy of neoliberal urban governance, where art is deployed as a tool for place-branding, tourism, and investment-friendly urban transformation. Through close visual analysis and contextual examination of commissioning frameworks, funding structures, and site selection, the paper argues that feminist and queer iconographies are incorporated into urban revitalization efforts in ways that often depoliticize their radical potential. Rather than challenging existing power relations, these interventions risk producing a form of curated inclusivity and visibility that dovetails gendered claims to citizenship with middle-class aesthetics and urban policy agendas of redevelopment.